2018
DOI: 10.1002/pchj.217
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between environmental sensitivity, ecological worldview, personal norms and pro‐environmental behaviors in Chinese children: Testing the value–belief–norm model with environmental sensitivity as an emotional basis

Abstract: This study addresses the relationships that ecological worldview, environmental sensitivity, and personal norms have with pro-environmental behaviors in a particular child population in urban China. The survey questionnaires were distributed to 410 Grade 6 students from eight Green Schools in Shenzhen, China. The sample included 223 (54.3%) boys and 187 (45.6%) girls with ages ranging from 10 to 13 years. The results from structural equation modelling reveal that environmental sensitivity and personal norms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Regarding satisfaction with life, we found that the members of the group with the highest scores were 7 times more likely to feel a higher degree of connectivity with nature. Considering that satisfaction with life is an indicator of well-being and, therefore, of health, this finding supports the positive and significant relationships between well-being, health, and connectivity with nature found in both adults [37,40,49] and children [35], although, in contrast with Wang and Kang's findings [16], it is only a reciprocal influence. In this vein, the results indicate that well-being is a relevant aspect to be considered in both public health agendas [50] and the United Nations SD agenda, i.e., the 2030 Agenda.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Regarding satisfaction with life, we found that the members of the group with the highest scores were 7 times more likely to feel a higher degree of connectivity with nature. Considering that satisfaction with life is an indicator of well-being and, therefore, of health, this finding supports the positive and significant relationships between well-being, health, and connectivity with nature found in both adults [37,40,49] and children [35], although, in contrast with Wang and Kang's findings [16], it is only a reciprocal influence. In this vein, the results indicate that well-being is a relevant aspect to be considered in both public health agendas [50] and the United Nations SD agenda, i.e., the 2030 Agenda.…”
Section: Discussionsupporting
confidence: 76%
“…Some research with children has focused on analyzing the role of experiences in natural environments and their relation to PEBs, finding positive relationships between them [33] and an increase in connectedness to nature [34]. Regarding age, connectedness to nature is related to PEBs in both adults [12,27,28] and children [35]. Moreover, rural environments and the proximity of nature to home have been associated with greater connectedness to nature and the fostering of PEBs in children [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study proposes love of nature as an antecedent variable of biospheric values, ecological worldview, and personal norms in terms of their relationships to GCBs. In an earlier study, Wu (2018) tested the relationships among ecological worldview, personal norms, love of nature, and general pro-environmental behavior among child populations in China. This study goes one step further by taking the value variables into consideration and examining the model among young adult populations (i.e., undergraduate students) in eastern China.…”
mentioning
confidence: 99%
“…Awareness of ecofeminist and ecocentric ethics affects environmental attitudes positively (Yalmancı & Gözüm, 2019). In a study conducted in China, it was reported that the impact of the ecological worldview is completely mediated by personal norms whereas environmental sensitivity is mediated by both personal norms and the ecological worldview (Lingqiong, 2018). The results of the present study suggest that the natural resource depletion risk is related to not holding the ecological worldview and to being more dependent on norms in developing environmental behaviors.…”
Section: Discussionmentioning
confidence: 42%